Novel Therapies for the Treatment of Drug-Induced Liver Injury: A Systematic Review - Benić, Mirjana Stanić; Nežić, Lana; Vujić-Aleksić, Vesna; Mititelu-Tartau, Liliana (Frontiers in Pharmacology, 2022)
Many drugs with different mechanisms of action and indications available on the market today are capable of inducing hepatotoxicity. Drug-induced liver injury (DILI) has been a treatment challenge nowadays as it was in the past. We searched Medline (via PubMed), CENTRAL, Science Citation Index Expanded, clinical trials registries and databases of DILI and hepatotoxicity up to 2021 for novel therapies for the management of adult patients with DILI based on the combination of three main search terms: (1) treatment, (2) novel, and (3) drug-induced liver injury. The mechanism of action of novel therapies, the potential of their benefit in clinical settings, and adverse drug reactions related to novel therapies were extracted. Cochrane Risk of bias tool and Grading of Recommendations Assessment, Development and Evaluation (GRADE) assessment approach was involved in the assessment of the certainty of the evidence for primary outcomes of included studies. One thousand three hundred seventy-two articles were identified. Twenty-eight articles were included in the final analysis. Eight randomized controlled trials (RCTs) were detected and for six the available data were sufficient for analysis. In abstract form only we found six studies which were also anaylsed. Investigated agents included: bicyclol, calmangafodipir, cytisin amidophospate, fomepizole, livina-polyherbal preparation, magnesium isoglycyrrhizinate (MgIG), picroliv, plasma exchange, radix Paeoniae Rubra, and S-adenosylmethionine. The primary outcomes of included trials mainly included laboratory markers improvement. Based on the moderate-certainty evidence, more patients treated with MgIG experienced alanine aminotransferase (ALT) normalization compared to placebo. Low-certainty evidence suggests that bicyclol treatment leads to a reduction of ALT levels compared to phosphatidylcholine. For the remaining eight interventions, the certainty of the evidence for primary outcomes was assessed as very low and we are very uncertain in any estimate of effect. More effort should be involved to investigate the novel treatment of DILI. Well-designed RCTs with appropriate sample sizes, comparable groups and precise, not only surrogate outcomes are urgently welcome.